2021
DOI: 10.1021/acs.jchemed.1c00445
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Engineering Teaching in COVID-19 Times: Successfully Adapting a Capstone Design Course to a Remote Format

Abstract: The coronavirus COVID-19 pandemic required educational institutions to adapt face-to-face to remote teaching. This study reports the experience in the first semester of 2020 for a Chemical Engineering Capstone Design Course at the University of Campinas in Brazil. In this course, senior year students develop a group project, in which they simulate a chemical plant and evaluate its technoeconomic feasibility. In 2020, the groups were proposed to design a process to replace diesel fuel from the bus fleet in Camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Recent studies have shown an increasing concern in the mental health of undergraduate students. The outbreak of the COVID-19 pandemic has forced universities to shut down to prevent the spread of the highly infectious disease. As a result of lockdown restrictions, face-to-face classes were switched to online learning . A study on engineering students has reported that the sudden switch of learning mode increased the prevalence of stress, anxiety, and depression among students .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown an increasing concern in the mental health of undergraduate students. The outbreak of the COVID-19 pandemic has forced universities to shut down to prevent the spread of the highly infectious disease. As a result of lockdown restrictions, face-to-face classes were switched to online learning . A study on engineering students has reported that the sudden switch of learning mode increased the prevalence of stress, anxiety, and depression among students .…”
Section: Discussionmentioning
confidence: 99%
“…As a result of lockdown restrictions, face-to-face classes were switched to online learning. 71 A study on engineering students has reported that the sudden switch of learning mode increased the prevalence of stress, anxiety, and depression among students. 72 It is necessary to monitor the mental health of students as it has an enormous impact on their learning.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Mining educational data opens the door to integrating artificial intelligence into teaching and learning processes and enables new approaches to address ongoing challenges in chemistry education: The COVID-19 pandemic has also demonstrated the need for remote learning tools for chemistry education. , A comprehensive analysis of the effective use of these educational resources can be enhanced by examining log files, especially when utilizing the provided digital features, which may not be immediately evident . Fine-grained log file data also allows for tracking and understanding learner interaction with assessment tasks, identifying factors that influence learning performance, and drawing conclusions on latent constructs such as learning strategies …”
Section: Introductionmentioning
confidence: 99%
“…For this transition, the university made available a series of tools that included tutorials and courses for the use of videoconferencing platforms . Due to the pandemic, several experiences in adapting courses to online delivery were reported. In these cases, technology aided learning by providing new ways of teaching and communicating with students. Learning is one of the most important tools in the training of any professional, and once achieved, it is possible to predict optimal labor performance .…”
Section: Introductionmentioning
confidence: 99%